AQ 1029－2017 Use and Management Specification of Coal Mine Safety Monitoring System and Testing Instrument (draft for approval) - SUN Jiping (Gong-kuang zidonghua, 2017)
The standard stipulates requirements of coal mine safety monitoring system and testing equipment, including the equipments, the design and installation, the sensor settings, the use and maintenance, the system and network information processing, the management system and technical information and so on. The standard is applicable to the nationwide underground coal mine, including mines of new construction, renovation and expansion.